Oliver O’Donovan on Politics and Eschatology in the Book of Revelation - Tae, Dong-Yaul (The expository times, 2026)
Oliver O’Donovan is well known for developing a political theology from an eschatological perspective based on the interpretation of the Book of Revelation. His political theology has drawn both praise and critique. Critics argue he creates an imbalance between the eschatological ‘already’ and ‘not-yet,’ relies too heavily on prayer and prophetic witness as tools against imperial powers, and depicts history as static, cyclical, or dualistic. This study, however, defends O’Donovan’s approach, asserting it faithfully reflects Revelation’s structure and content. It demonstrates that he effectively integrates the ‘already’ and ‘not-yet,’ particularly through his interpretation of Revelation 21 and 22, highlighting their deep interconnection. Furthermore, it argues that O’Donovan sees prayer and prophetic witness as profoundly powerful, not weak. While acknowledging circular and dual elements in his portrayal of history, the study contends that his eschatology avoids static or dualistic logic. Instead, it emphasizes dynamic processes central to eschatology, such as redemption, restoration, transformation, and consummation, and their intricate interrelationships.